Clinical outcomes of percutaneous coronary intervention for de novo lesions in small coronary arteries: A systematic review and network meta-analysis - Ma, Wen-Rui; Chandrasekharan, Karthik H.; Nai, Chang-Sheng; Zhu, Yong-Xiang; Iqbal, Javaid; Chang, Shang; Cheng, You-Wei; Wang, Xin-Yu; Bourantas, Christos V.; Zhang, Yao-Jun (Frontiers in Cardiovascular Medicine, 2022)
Background Percutaneous coronary intervention (PCI) has a well-established role in revascularization for coronary artery disease. We performed network meta-analysis to provide evidence on optimal intervention strategies for de novo lesions in small coronary arteries. Materials and methods Enrolled studies were randomized clinical trials that compared different intervention strategies [balloon angioplasty (BA), biolimus-coated balloon (BCB), bare-metal stent (BMS), new-generation drug-eluting stent (New-DES), older generation sirolimus-eluting stent (Old-SES), paclitaxel-coated balloon (PCB), and paclitaxel-eluting stent (PES)] for de novo lesions in small coronary arteries. The primary outcome was major adverse cardiac events (MACE). Results A total of 23 randomized clinical trials comparing seven intervention devices were analyzed. In terms of the primary outcome, New-DES was the intervention device with the best efficacy [surface under the cumulative ranking curve (SUCRA), 89.1%; mean rank, 1.7], and the Old-SES [risk ratio (RR), 1.09; 95% confidence interval (CI), 0.45–2.64] and PCB (RR, 1.40; 95% CI, 0.72–2.74) secondary to New-DES, but there was no statistically significant difference between these three intervention devices. All DES and PCB were superior to BMS and BA for MACE in both primary and sensitivity analysis. For secondary outcomes, there was no association between all-cause mortality and myocardial infarction (MI) with any intervention strategy, and additionally, the findings of target lesion revascularization (TLR) were similar to the primary outcomes. Conclusion Paclitaxel-coated balloon yielded similar outcomes to New-DES for de novo lesions in small coronary arteries. Therefore, this network meta-analysis may provide potential support for PCB as a feasible, effective, and safe alternative intervention strategy for the revascularization of small coronary arteries. Systematic review registration [https://www.crd.york.ac.uk/PROSPERO/#recordDetails], identifier [CRD42022338433].